Proyecto de factibilidad para la creación de una empresa de Pastelería en Fondant y su comercialización en la ciudad de Loja - Lima Jaramillo, Richard Javier (2015)
This research was conducted in the city of Loja, having as main objective the study of "FEASIBILITY FOR CREATING A COMPANY IN PASTRY fondant and marketing in the city of Loja" This project is to form a producer and marketer fondant cake company in the city of Loja, with a quality and unique designs, where our customers have the option to choose the flavor you want the cake and all the design that is the hallmark principal of our company, as they can be custom or unique to each client. For this research a market study, which could determine the feasibility of the project feasibility for the creation of a company of pastry Fondant in the city of Loja, for which we proceeded to conduct field work surveying was carried out 397 potential customers, these surveys were made randomly, ie at different times and places, in order to collect reliable and accurate information, and later proceed to tabulating the data and analyze the feasibility of this project. Our company aims to cater to 56.741 families in the city of Loja, who are our potential demand as indicated by the sample population that was determined in the first part of our investigation. Also of that investigation, we obtained the result that talking about our product (Fondant Cakes) our effective demand is 352,973 cakes a year, our retail price is $ 35.00, where it is taken as reference cakes 20 portions that are the most sought after on the market. As for the project engineering process route was presented in all its phases, all about the size and location, and the plane of physical layout of the plant, also it indicated that the production plant will be located in the Citadel's Band of the city of Loja streets: Vilcabamba and Manuela Saenz north of the city and its local display and sales at Olmedo and Rocafuerte (Downtown) It is necessary for the development of this research analyze the financial study, where the amount of the initial investment will be $ 61,668.46, as well as indicators of financial evaluation so that it is determined whether or not the company is determined to ride . According to the financial evaluation and according to the results determine the profitability and viability of this project and in which their conclusions and recommendations will be determined